Porous hollow carbon material, porous carbon / gamma-MnO2 electrode material as well as preparation method and application of porous carbon / gamma-MnO2 electrode material

By preparing porous hollow carbon materials combined with electrolytic manganese dioxide, the electron/ion transmission efficiency of γ-MnO2 is improved, and the problems of poor conductivity of manganese dioxide and slow diffusion kinetics during the charge and discharge process are solved, thereby improving the battery rate performance and cycle stability.

CN119735190APending Publication Date: 2025-04-01HUNAN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411863490.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Manganese dioxide has poor conductivity during charging and discharging and partially dissolved in the electrolyte, which affects the rate performance and cycle stability of the battery. At the same time, the Zn2+ diffusion kinetics are slow, resulting in irreversible phase change and material structure damage.

Method used

Porous hollow carbon materials are prepared by hydrothermal method and combined with electrolytic manganese dioxide to improve the electron/ion transport efficiency of γ-MnO2. The specific steps include reacting resorcinol with a silicate template, carbonizing and etching, preparing porous hollow carbon spheres, and then doping them with commercial electrolytic manganese dioxide to prepare porous carbon/γ-MnO2 electrode material.

Benefits of technology

It improves the rate performance and cycle stability of the battery, enhances the transmission efficiency of zinc ions, avoids the agglomeration of γ-MnO2, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735190A_ABST
    Figure CN119735190A_ABST
Patent Text Reader

Abstract

The invention discloses a porous hollow carbon material, a porous carbon / gamma-MnO2 electrode material and a preparation method and application thereof, and relates to the technical field of aqueous rechargeable zinc ion batteries. The preparation method of the porous hollow carbon material comprises the following steps: S1, dissolving resorcinol in a mixed solution of ethanol and water, adding an ammonia water solution, tetraethoxysilane and a formaldehyde solution into the solution, and stirring at room temperature; s2, transferring the mixed solution into a reaction container, and reacting at 100-180 DEG C to obtain a red brown pasty substance; s3, centrifuging and drying the red brown pasty substance to obtain red brown powder; and S4, putting a product obtained in the step S3 into a heating container for heat treatment, taking out the product after furnace cooling, and etching at room temperature to obtain the porous hollow carbon material. The porous hollow carbon material prepared by the scheme has relatively high specific surface area and relatively strong adsorption capacity, and can be combined with electrolytic manganese dioxide to improve the electron / ion transmission efficiency of gamma-MnO2, so that the rate capability of a battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aqueous rechargeable zinc ion batteries, and in particular to a porous hollow carbon material, a porous carbon / γ-MnO2 electrode material, and a preparation method and application thereof. Background Art

[0002] With the gradual emergence of global environmental pollution, extreme climate and traditional energy shortage, the development of sustainable and renewable new energy and its storage technology has become a global priority. Lithium-ion batteries dominate the current rechargeable battery market with their high energy density and mature preparation technology. However, the current shortage of lithium metal resources, toxicity, corrosion, flammability and explosion have stimulated people's research on greener and more environmentally friendly materials. Zinc-ion batteries have become a hot topic of development and research in recent years due to their high theoretical capacity (820mAh / g), high power density, efficient and safe discharge process, non-toxic and cheap battery materials, and simple preparation process. However, due to the strong charge repulsion and inherent slow kinetics between multivalent ions and electrode materials during the charging and discharging process, there are relatively few truly suitable aqueous zinc-ion materials. At present, MnO2, Prussian blue analogs and vanadium-based oxides are widely used in aqueous zinc-ion batteries. Among them, manganese oxides with layered structures have attracted much attention due to their high theoretical capacity (308mAh / g), low toxicity, large voltage window (about 2V), and high output voltage (about 1.3V).

[0003] Manganese dioxide has poor intrinsic conductivity and will partially dissolve in the electrolyte during the charge and discharge process, thus affecting the rate performance and cycle stability of the battery. 2+ It has a large radius and charge density, which leads to relatively slow diffusion kinetics, and in the process of charge and discharge, Zn 2+ It is difficult to escape from the positive electrode, resulting in irreversible phase change, which ultimately destroys the material structure and will further cause the battery's capacity attenuation, cycle stability and rate performance to deteriorate.

[0004] Therefore, how to improve the conductivity of manganese dioxide and improve its electrochemical properties has become a technical problem that needs to be solved urgently. Summary of the invention

[0005] One of the purposes of the present invention is to provide a method for preparing a porous carbon material, wherein an organic precursor is prepared by a hydrothermal method, and resorcinol is covered on the surface using a silicate as a template, followed by carbonization and etching to prepare porous nanocarbon balls. The material has a high specific surface area and strong adsorption capacity, and can be combined with electrolytic manganese dioxide to improve the electron / ion transmission efficiency of γ-MnO2, thereby improving the rate performance of the battery.

[0006] In order to achieve the above object, the present invention adopts the following technical scheme: A method for preparing a porous hollow carbon material comprises the following steps: S1. Dissolve resorcinol in a mixed solution of ethanol (such as anhydrous ethanol) and water (such as deionized water), add ammonia solution, tetraethyl orthosilicate (TEOS) and formaldehyde solution to the solution, and stir at room temperature (25°C) (such as stirring for 6 hours); then, tetraethyl orthosilicate may be added dropwise to the solution and stirring may be continued (such as continuing stirring for 12 hours); S2. The mixed solution was transferred to a reaction vessel and reacted at 100 to 180° C. to obtain a reddish brown paste; S3. The reddish brown paste was centrifuged and dried to obtain a reddish brown powder; S4. placing the product obtained in step S3 in a heating container for heat treatment, taking it out after cooling in the furnace, and etching (such as acid etching) at room temperature to obtain hollow carbon spheres (i.e., porous hollow carbon materials).

[0007] Furthermore, in step S1, the mass fraction of the ammonia solution is 28 wt %.

[0008] Furthermore, in step S1, the mass fraction of the formaldehyde solution is 37wt%.

[0009] Furthermore, in step S1, in the mixed solution of ethanol and water, the volume ratio of ethanol to water is 7:1.

[0010] Furthermore, in step S1, every 0.1 g of resorcinol corresponds to 20 ml of a mixed solution of ethanol and water.

[0011] Furthermore, in step S1, the volume ratio of the aqueous ammonia solution to the mixed solution of ethanol and water is 3:80.

[0012] Furthermore, in step S1, the volume ratio of the tetraethyl orthosilicate to the formaldehyde solution is 5:1.

[0013] Furthermore, in step S1, the volume ratio of the mixed solution of ethanol and water to the mixed solution of formaldehyde solution and tetraethyl orthosilicate is 80:3.36.

[0014] Furthermore, in step S2, the reaction time at 100-180° C. is 24 h.

[0015] Furthermore, in step S4, the temperature of the heat treatment (such as calcination) is 700° C. and the time is 3 hours.

[0016] Furthermore, in step S4, a hydrofluoric acid (HF acid) aqueous solution with a mass fraction of 20 wt % is used for etching, and the etching time is 12 h.

[0017] The reaction container involved in the above method can be a high-temperature reactor made of polytetrafluoroethylene. The heating container involved in the above method can be a constant-temperature tube furnace.

[0018] The second object of the present invention is to provide a porous hollow carbon material, which is prepared by the above-mentioned method for preparing the porous hollow carbon material.

[0019] The third object of the present invention is to provide a method for industrially preparing porous carbon / γ-MnO2 electrode materials based on commercial electrolytic manganese dioxide. The method uses commercial electrolytic manganese dioxide (EMD) and porous hollow carbon spheres as raw materials to prepare electrode material particles with high specific surface area that can meet the needs of power batteries. The porous hollow carbon spheres are simply doped with industrial-grade manganese dioxide (i.e., industrial commercial electrolytic manganese dioxide) to prepare positive electrode materials with better performance, which is beneficial to industrial promotion.

[0020] In order to achieve the above object, the present invention adopts the following technical scheme: a method for preparing porous carbon / γ-MnO2 electrode material based on EMD, comprising the following steps: 1. Pour EMD (commercial electrolytic manganese dioxide) and ethanol into a ball mill for ball milling to obtain a gray-black paste, which is then washed and dried to obtain black powder γ-MnO2; 2. Disperse γ-MnO2 (the black powder in step 1, i.e., EDM after ball milling) and porous hollow carbon material in isopropanol, form a suspension after ultrasonic treatment, vacuum filter the suspension to obtain black powder, and dry the black powder to obtain porous carbon / γ-MnO2 electrode material.

[0021] Step 1 can be understood as the industrialization of commercial electrolytic manganese dioxide, and industrial-grade electrolytic manganese dioxide is prepared by ball milling.

[0022] Furthermore, in step 1, the ball milling time is 9 h to 10 h, and during this period the material temperature is controlled not to exceed 100° C.

[0023] Furthermore, in step 1, during the ball milling process, the rotation speed of the ball mill is 150 r / min to 200 r / min.

[0024] Furthermore, in step 2, the mass ratio of the γ-MnO2 and the porous hollow carbon material is 4:1.

[0025] Furthermore, in step 2, every 10 ml of isopropanol corresponds to 50 mg of the mixture of γ-MnO2 and the porous hollow carbon material.

[0026] Among them, in step 1, the specific steps of washing and drying include: washing the obtained product (gray-black paste) with deionized water for several times, and then putting it into a forced air drying oven and drying it at 80° C. for 12 hours.

[0027] A fourth object of the present invention is to provide a porous carbon / γ-MnO2 electrode material, which is prepared by the above-mentioned method for preparing porous carbon / γ-MnO2 electrode material based on EMD.

[0028] In addition, the porous carbon / γ-MnO2 electrode material can be used in the preparation of zinc ion batteries. For example, the porous carbon / γ-MnO2 electrode material is used as the positive electrode material of the zinc ion battery.

[0029] The present invention has the following beneficial effects: First, the present invention uses silicate as a template, and later uses chemical etching to remove the silicon core to make a porous carbon material (i.e., a porous hollow carbon material). The operation is convenient, the preparation method is simple, the price is low, and the process is easy to control, which is conducive to large-scale production. At the same time, the prepared porous carbon material has a high specific surface area, strong adsorption, and a wide range of applications.

[0030] It is worth mentioning that the present invention prepares porous carbon with a multi-shell core-layer structure through a hydrothermal method, which has a three-dimensional structure. Combining it with electrolytic manganese dioxide can effectively improve the electron / ion transmission efficiency of γ-MnO2, thereby improving the rate performance of the battery.

[0031] Secondly, the present invention uses commercial electrolytic manganese dioxide (EMD) and porous hollow carbon spheres (i.e., porous hollow carbon materials) as raw materials to prepare electrode material particles with high specific surface area that can meet the needs of power batteries, and simply dopes the porous hollow carbon spheres with industrial-grade manganese dioxide (i.e., EMD after ball milling) to prepare positive electrode materials with better performance, which is beneficial to industrial promotion.

[0032] Then, the porous carbon / γ-MnO2 electrode material prepared by the method provided by the present invention can effectively solve the problem of low capacity of manganese-based materials during charging and discharging, and the γ-MnO2 is evenly attached to the surface of the porous carbon spheres, which can effectively avoid the agglomeration of γ-MnO2, improve the transmission efficiency of zinc ions, and enhance the ion dynamics of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 XRD patterns of electrolytic manganese dioxide and porous carbon / γ-MnO2 composite materials in Example 1; Figure 2 is the XRD pattern of the porous carbon material in Example 1; Figure 3 is the CV curve of the porous carbon / γ-MnO2 composite material in Example 1; Figure 4 The charge-discharge cycle diagram of the porous carbon / γ-MnO2 composite material in Example 1 at 0.1C, 0.2C, 0.5C, 1C, 2C, and 5C rates; Figure 5 and Figure 6 is a SEM image of the porous carbon material in Example 1, wherein: Figure 5 From a macro perspective, Figure 6 For microscopic perspective; Figure 7 and Figure 8 is a SEM image of the porous carbon / γ-MnO2 composite material in Example 1, wherein: Figure 7 From a macro perspective, Figure 8 A microscopic perspective. DETAILED DESCRIPTION

[0034] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with the examples, and the contents mentioned in the examples are not limitations of the present invention. It should be noted in advance that the following examples were completed in the laboratory, and those skilled in the art should understand that the amounts of the components given in the examples only represent the ratio relationship between the components, rather than specific limitations.

[0035] Porous carbon materials have the advantages of carbon materials, such as high chemical stability, good electrical conductivity, low price, etc.; at the same time, porous carbon materials also have the advantages of high specific surface area, adjustable pore structure, etc. Porous carbon materials are widely used in the fields of ion battery electrodes, supercapacitors, photovoltaic materials, catalyst carriers, etc., and are a new type of carbon material with great development potential and application prospects. The present invention prepares an organic precursor by a hydrothermal method, and uses silicate as a template to cover the surface with resorcinol, followed by carbonization and etching to produce porous nano-carbon spheres with high specific surface area and strong adsorption capacity.

[0036] On the one hand, the present invention provides a method for preparing a porous hollow carbon material, which is mainly based on the following concept: using a hydrothermal method and an asynchronous sequential nucleation method, an organic precursor is prepared by a hydrothermal method, and the precursor presents an uneven spherical shape, followed by carbonization and chemical etching, and the silicon core is removed by etching on the original basis, so that it presents a hollow carbon sphere. The combination of the uneven surface and the hollow carbon sphere makes it have a high specific surface area and strong adsorption capacity.

[0037] The method for preparing the porous hollow carbon material provided by the present invention mainly comprises the following steps: S1. Dissolve resorcinol in a mixed solution of ethanol (such as anhydrous ethanol) and water (such as deionized water), add ammonia water (28wt%) solution, tetraethyl orthosilicate (TEOS) and formaldehyde (37wt%) solution to the solution, stir at room temperature (25°C) for 6 hours, then drop tetraethyl orthosilicate into the solution and continue stirring for 12 hours; S2. The mixed solution was transferred to a reaction vessel and reacted at 100-180°C for 24 hours to obtain a reddish brown paste; S3. The reddish brown paste was centrifuged and dried to obtain a reddish brown powder; S4. The product obtained in step S3 is placed in a heating container for heat treatment (temperature of 700°C, time of 3 hours), taken out after cooling in the furnace, and acid-etched at room temperature to obtain a porous hollow carbon material.

[0038] In step S1, in the mixed solution of ethanol and water, the volume ratio of ethanol to water is 7:1.

[0039] In step S1, every 0.1 g of resorcinol corresponds to 20 ml of a mixed solution of ethanol and water.

[0040] In step S1, the volume ratio of the aqueous ammonia solution to the mixed solution of ethanol and water is 3:80.

[0041] In step S1, the volume ratio of ethyl orthosilicate to formaldehyde solution is 5:1.

[0042] In step S1, the volume ratio of the mixed solution of ethanol and water to the mixed solution of formaldehyde solution and tetraethyl orthosilicate is 80:3.36.

[0043] In step S4, a hydrofluoric acid (HF acid) aqueous solution with a mass fraction of 20 wt % is used for etching, and the etching time is 12 h.

[0044] The above preparation method uses a silicate template and later uses chemical etching to remove the silicon core to make a porous carbon material. The operation is convenient, the preparation method is simple, the price is low, the process is easy to control, and it is conducive to large-scale production. At the same time, the prepared porous carbon material has a high specific surface area, strong adsorption, and a wide range of applications.

[0045] On the other hand, the present invention also provides a method for industrial preparation of porous carbon / γ-MnO2 electrode materials based on commercial electrolytic manganese dioxide, which is mainly based on the following concept: preparing silicate template microspheres, removing the silicon core in the silicate microsphere template by carbonization and acid etching, leaving porous hollow carbon microspheres. Then, the porous carbon and commercial electrolytic manganese dioxide are ultrasonically treated to make the electrolytic manganese dioxide uniformly adhere to the porous carbon surface, increase the specific surface area, improve the ion transmission efficiency, and thus improve the battery performance.

[0046] The method for preparing porous carbon / γ-MnO2 electrode material based on EMD provided by the present invention mainly comprises the following steps: 1. Pour EMD (commercial electrolytic manganese dioxide) and ethanol into the ball mill of the ball mill and seal it to obtain a gray-black paste. Wash the obtained product with deionized water several times, put it into a blast drying oven, and dry it at 80°C for 12 hours to obtain black powder γ-MnO2. 2. Disperse γ-MnO2 (black powder in step 1) and porous hollow carbon material in isopropanol, form a suspension after ultrasonic treatment, vacuum filter the suspension to obtain black powder, dry the black powder to obtain porous carbon / γ-MnO2 electrode material.

[0047] In step 1, the ball milling time is 9 h to 10 h, and during this period the material temperature is controlled not to exceed 100° C.

[0048] In step 1, during the ball milling process, the rotation speed of the ball mill is 150 r / min to 200 r / min.

[0049] In step 2, the mass ratio of γ-MnO2 and the porous hollow carbon material is 4:1.

[0050] In step 2, every 10 ml of isopropanol corresponds to 50 mg of the mixture of γ-MnO2 and the porous hollow carbon material.

[0051] The above preparation method uses commercial electrolytic manganese dioxide (EMD) and porous hollow carbon spheres as raw materials to prepare electrode material particles with high specific surface area that can meet the needs of power batteries. The porous hollow carbon spheres are simply doped with industrial-grade manganese dioxide (EMD after ball milling) to prepare positive electrode materials with better performance, which is beneficial to industrial promotion.

[0052] The following is further explained with specific examples.

[0053] Example 1 1. Preparation of porous carbon / γ-MnO2 positive electrode material.

[0054] 1. Weigh 0.4g of resorcinol and dissolve it in a mixed solution of 70ml of anhydrous ethanol and 10ml of deionized water. Add 3.0ml of ammonia (28wt%) solution to the solution, then drop 2.8ml of tetraethyl orthosilicate (TEOS) and 0.56ml of formaldehyde (37wt%) solution in sequence. Stir the mixed solution at room temperature (25℃) for 6h, then drop 1.5mL of tetraethyl orthosilicate into the solution and continue stirring for 12h.

[0055] 2. The mixed solution was then transferred to a polytetrafluoroethylene high-temperature reactor and reacted at 100°C for 24 hours to obtain a reddish-brown paste.

[0056] 3. After centrifugation, the paste obtained by the reaction was placed in a forced air drying oven at 50°C and dried overnight.

[0057] 4. The obtained product is then placed in a constant temperature tubular furnace and heat treated at 700°C under argon atmosphere. After cooling in the furnace, the obtained material is taken out and etched with a 20wt% HF acid aqueous solution at room temperature for 12 hours to obtain the desired hollow carbon spheres.

[0058] 5. Weigh 5g (1 mol) of electrolytic manganese dioxide (EDM) and 5ml of ethanol. Pour EDM and ethanol into the ball mill of the planetary ball mill, add zirconium beads, and the ball-to-material ratio is about 4:1. After sealing and pressing, ball mill at a speed of 150 r / min to finally obtain a gray-black paste. Wash the obtained product with deionized water several times, put it into a blast drying oven, and dry it at 80℃ for 12h to obtain a black powder.

[0059] 6. Take 40 mg of industrial electrolytic manganese dioxide γ-MnO2 (the black powder in step 5, i.e., EDM after ball milling) and 10 mg of hollow carbon spheres and disperse them in 10 mL of isopropanol. Ultrasonic treatment is performed for 2 h to form a uniform suspension, and the suspension is vacuum filtered to obtain a black powder. Finally, the black powder is dried in a vacuum oven at 60 ° C for 24 h to obtain a porous carbon / γ-MnO2 composite cathode material.

[0060] 2. Product description.

[0061] Figure 1 The XRD patterns of electrolytic manganese dioxide and porous carbon / γ-MnO2 composite materials in the embodiment are shown in the figure. As can be seen from the figure, manganese dioxide and porous carbon / γ-MnO2 composite materials are completely consistent with the JCPDS standard pattern PDF card number #30-0820. As can be seen from the figure, the characteristic peaks of the material are clearly shown, indicating that its crystallinity is good. There are no impurity peaks, indicating that the purity is high.

[0062] Figure 2 The XRD spectrum of the porous carbon sphere in the embodiment is completely consistent with the JCPDS standard spectrum PDF card number #50-0926, indicating that the prepared material is porous carbon.

[0063] Figure 5 and Figure 6 is a SEM image of the porous carbon material in the embodiment. Figure 5 From a macro perspective, Figure 6 From the microscopic perspective, we can see that the 3D micro-nanostructure is self-assembled from small primary particles into micron-sized spheres, which helps to improve the electrochemical performance of the material. The size is about 100nm-1um.

[0064] Figure 7 and Figure 8 : This is the SEM image of the porous carbon / γ-MnO2 composite material in the embodiment. Figure 7 From a macro perspective, Figure 8 A microscopic perspective.

[0065] 3. Electrochemical performance test of the product.

[0066] First, the prepared porous carbon / γ-MnO2 composite material, conductive carbon black and polyvinylidene fluoride were mixed evenly in a mass ratio of 7:2:1 and coated on a stainless steel mesh, punched and cut into pieces, and vacuum dried at 80℃ for 12h to make the positive electrode. Zinc sheet was used as the negative electrode, the electrolyte concentration was 2M ZnSO4+0.1M MnSO4, and the diaphragm was glass fiber. The button cell was assembled, and the electrochemical performance of the porous carbon / γ-MnO2 composite material was tested under the charge and discharge voltage conditions of 1.0V-1.9V.

[0067] Test results see Figure 3 , 4 As shown. Figure 3 The CV curve of porous carbon / γ-MnO2 composite material. Two pairs of redox peaks can be observed in the figure (reduction peak: 1.24 and 1.38V, oxidation peak: 1.54 and 1.60V), which is consistent with the H peak of MnO2 during the discharge / charge process. + and Zn 2+ The embedding and ejection process is consistent. Figure 4 The following is a charge and discharge cycle diagram of the porous carbon / γ-MnO2 composite material at 0.1C, 0.2C, 0.5C, 1C, 2C, and 5C rates. As can be seen from the figure, at a rate of 1C, the porous carbon / γ-MnO2 composite material can provide a discharge capacity of about 235mAh / g, and at a rate of 5C, the discharge capacity is still 18mAh / g. After experiencing various rates, especially high-rate cycles, the material still has a specific capacity of 132mAh / g at a rate of 0.1C. This shows that the material has good stability and large capacity, which can meet the needs of power batteries. Example 2

[0068] The raw materials and equipment used in this embodiment are the same as those in Example 1, and will not be described in detail here. The main difference between this embodiment and Example 1 is the different hydrothermal temperature. Similar to Example 1, the process of preparing porous carbon / γ-MnO2 composite positive electrode material in this embodiment also includes the following steps: 1. Weigh 0.4g of resorcinol and dissolve it in a mixed solution of 70ml of anhydrous ethanol and 10ml of deionized water. Add 3.0ml of ammonia (28wt%) solution to the solution, then drop 2.8ml of tetraethyl orthosilicate (TEOS) and 0.56ml of formaldehyde (37wt%) solution in sequence. Stir the mixed solution at room temperature (25℃) for 6h, then drop 1.5mL of tetraethyl orthosilicate into the solution and continue stirring for 12h.

[0069] 2. The mixed solution was then transferred to a polytetrafluoroethylene high-temperature reactor and reacted at 150°C for 24 hours to obtain a reddish-brown paste.

[0070] 3. After centrifugation, the paste obtained by the reaction was placed in a forced air drying oven at 50°C and dried overnight.

[0071] 4. The obtained product is then placed in a constant temperature tubular furnace and heat treated at 700°C under argon atmosphere. After cooling in the furnace, the obtained material is taken out and etched with a 20wt% HF acid aqueous solution at room temperature for 12 hours to obtain the desired hollow carbon spheres.

[0072] 5. Weigh 5g (1 mol) of electrolytic manganese dioxide (EDM) and 5ml of ethanol. Pour EDM and ethanol into the ball mill of the planetary ball mill, add zirconium beads, and the ball-to-material ratio is about 4:1. After sealing and pressing, ball mill at a speed of 150 r / min to finally obtain a gray-black paste. Wash the obtained product with deionized water several times, put it into a blast drying oven, and dry it at 80℃ for 12h to obtain a black powder.

[0073] 6. Take 40 mg of industrial electrolytic manganese dioxide γ-MnO2 (black powder in step 5) and 10 mg of hollow carbon spheres and disperse them in 10 mL of isopropanol. Ultrasonic treatment is performed for 2 h to form a uniform suspension, and the suspension is vacuum filtered to obtain black powder. Finally, the black powder is dried in a vacuum oven at 60 ° C for 24 h to obtain a porous carbon / γ-MnO2 composite positive electrode material. The product was tested for electrochemical properties in the same manner as in Example 1, and the test results are shown in Table 1. Example 3

[0074] The raw materials and equipment used in this embodiment are the same as those in Example 1. The main difference between this embodiment and Example 1 is that the hydrothermal temperature is slightly different. The process of preparing the porous carbon / γ-MnO2 composite positive electrode material in this embodiment also includes the following steps: 1. Weigh 0.4g of resorcinol and dissolve it in a mixed solution of 70ml of anhydrous ethanol and 10ml of deionized water. Add 3.0ml of ammonia (28wt%) solution to the solution, then drop 2.8ml of tetraethyl orthosilicate (TEOS) and 0.56ml of formaldehyde (37wt%) solution in sequence. Stir the mixed solution at room temperature (25℃) for 6h, then drop 1.5mL of tetraethyl orthosilicate into the solution and continue stirring for 12h.

[0075] 2. The mixed solution was then transferred to a polytetrafluoroethylene high-temperature reactor and reacted at 180°C for 24 hours to obtain a reddish-brown paste.

[0076] 3. After centrifugation, the paste obtained by the reaction was placed in a forced air drying oven at 50°C and dried overnight.

[0077] 4. Finally, the obtained product was placed in a constant temperature tubular furnace and heat treated at 700°C under argon atmosphere. After cooling in the furnace, the obtained material was taken out and etched with a 20 wt% HF acid aqueous solution at room temperature for 12 hours to obtain the desired hollow carbon spheres.

[0078] 5. Weigh 5g (1 mol) of electrolytic manganese dioxide (EDM) and 5ml of ethanol. Pour EDM and ethanol into the ball mill of the planetary ball mill, add zirconium beads, and the ball-to-material ratio is about 4:1. After sealing and pressing, ball mill at a speed of 150 r / min to finally obtain a gray-black paste. Wash the obtained product with deionized water several times, put it into a blast drying oven, and dry it at 80℃ for 12h to obtain a black powder.

[0079] 6. Take 40 mg of industrial electrolytic manganese dioxide γ-MnO2 (black powder in step 5) and 10 mg of hollow carbon spheres and disperse them in 10 mL of isopropanol. Ultrasonic treatment is performed for 2 h to form a uniform suspension, and the suspension is vacuum filtered to obtain black powder. Finally, the black powder is dried in a vacuum oven at 60 ° C for 24 h to obtain a porous carbon / γ-MnO2 composite positive electrode material. The product was tested for electrochemical properties in the same manner as in Example 1, and the test results are shown in Table 1. Comparative Example 1

[0080] The steps for preparing the porous carbon / γ-MnO2 composite positive electrode material in this comparative example are the same as those in Example 1, with the key difference being that industrial-grade electrolytic manganese dioxide (i.e., electrolytic manganese dioxide that is not ball-milled) is used instead of the electrolytic manganese dioxide that is ball-milled in Example 1. The process for preparing the porous carbon / γ-MnO2 composite positive electrode material in this comparative example includes: 1. Weigh 0.4g of resorcinol and dissolve it in a mixed solution of 70ml of anhydrous ethanol and 10ml of deionized water. Add 3.0ml of ammonia (28wt%) solution to the solution, then drop 2.8ml of tetraethyl orthosilicate (TEOS) and 0.56ml of formaldehyde (37wt%) solution in sequence. Stir the mixed solution at room temperature (25℃) for 6h, then drop 1.5mL of tetraethyl orthosilicate into the solution and continue stirring for 12h.

[0081] 2. The mixed solution was then transferred to a polytetrafluoroethylene high-temperature reactor and reacted at 100°C for 24 hours to obtain a reddish-brown paste.

[0082] 3. After centrifugation, the paste obtained by the reaction was placed in a forced air drying oven at 50°C and dried overnight.

[0083] 4. The obtained product was then placed in a constant temperature tubular furnace and heat treated at 700°C under argon atmosphere. After cooling in the furnace, the obtained material was taken out and etched with a 20 wt% HF acid aqueous solution at room temperature for 12 hours to obtain the desired hollow carbon spheres.

[0084] 5. Take 40 mg of industrial electrolytic manganese dioxide γ-MnO2 (not ball-milled) and 10 mg of hollow carbon spheres and disperse them in 10 mL of isopropanol. Ultrasonic treatment is performed for 2 h to form a uniform suspension, and the suspension is vacuum filtered to obtain a black powder. Finally, the black powder is dried in a vacuum oven at 60 ° C for 24 h to obtain the target product. The electrochemical performance test is performed according to the method in Example 1, and the test results are shown in Table 1. Comparative Example 2

[0085] The steps for preparing the porous carbon / γ-MnO2 composite positive electrode material in this comparative example are the same as those in Example 2, with the key difference being that industrial-grade electrolytic manganese dioxide (i.e., electrolytic manganese dioxide not ball-milled) is used instead of the electrolytic manganese dioxide ball-milled in Example 2. To simplify the description, the detailed preparation process is not repeated here. The electrochemical performance test method of the product obtained in this comparative example is the same as that in Example 2, and the test results are shown in Table 1. Comparative Example 3

[0086] The steps for preparing the porous carbon / γ-MnO2 composite positive electrode material in this comparative example are the same as those in Example 3, with the key difference being that industrial-grade electrolytic manganese dioxide (i.e., electrolytic manganese dioxide not ball-milled) is used instead of the electrolytic manganese dioxide ball-milled in Example 3. To simplify the description, the detailed preparation process is not repeated here. The electrochemical performance test method of the product obtained in this comparative example is the same as that in Example 3, and the test results are shown in Table 1. Comparative Example 4

[0087] In this comparative example, the zinc ion positive electrode material is ball-milled electrolytic manganese dioxide (EMD), and the electrochemical performance of the EMD is tested in the manner described in Example 1. The test results are shown in Table 1. Comparative Example 5

[0088] In this comparative example, the zinc ion positive electrode material is unmilled electrolytic manganese dioxide (EMD), and the electrochemical performance thereof is tested in the manner described in Example 1. The test results are shown in Table 1.

[0089] Table 1 Electrochemical performance test results of various embodiments and comparative examples

[0090] It can be seen from the above test results that Examples 1-3 prepared porous carbon / γ-MnO2 composite positive electrode materials with good morphological consistency and cycle stability at different hydrothermal temperatures. By comparing and analyzing the process conditions and product performance test results of Examples 1-3 and Comparative Examples 1-5, it can be seen that after ball milling, the prepared porous carbon / γ-MnO2 composite positive electrode material has a greatly improved performance compared to pure manganese dioxide as the positive electrode material. It can be seen that the porous hollow carbon spheres effectively improve the γ-MnO2 electron / ion transmission efficiency, thereby improving the rate performance of the battery. The reason may be that in the ball milling process of Examples 1-3, the hydrothermal method and the asynchronous successive nucleation method are used to remove the silicon core and the silicon shell by chemical etching to prepare hollow carbon microspheres, and then the porous carbon / γ-MnO2 composite material is prepared by ultrasonic dispersion and other treatments, wherein manganese dioxide is uniformly attached to the surface of the porous carbon spheres, effectively avoiding the agglomeration of manganese dioxide, improving the ion diffusion efficiency, and the three-dimensional porous network helps to provide electronic conductivity and provide a stable support.

[0091] In summary, the present invention uses commercial electrolytic manganese dioxide (EMD) and porous hollow carbon spheres as raw materials to prepare electrode material particles with high specific surface area that can meet the needs of power batteries, and simply dopes the porous hollow carbon spheres with industrial-grade manganese dioxide (i.e., electrolytic manganese dioxide after ball milling) to prepare positive electrode materials with better performance, which is beneficial to industrial promotion.

[0092] The above embodiments are preferred implementation schemes of the present invention. In addition, the present invention may also be implemented in other ways. Any obvious replacement without departing from the concept of the present technical solution is within the protection scope of the present invention.

[0093] Finally, it should be emphasized that in order to allow ordinary technicians in the field to more easily understand the improvements of the present invention over the prior art, some descriptions of the present invention have been simplified, and for the sake of clarity, some other elements are omitted in this application document. Those skilled in the art should realize that these omitted elements may also constitute the content of the present invention.

Claims

1. A method for preparing a porous hollow carbon material, characterized in that: The steps include: S1. Dissolve resorcinol in a mixed solution of ethanol and water, add an aqueous ammonia solution, ethyl orthosilicate and formaldehyde solution to the solution, and stir at room temperature; S2. The mixed solution was transferred to a reaction vessel and reacted at 100 to 180° C. to obtain a reddish brown paste; S3. The reddish brown paste was centrifuged and dried to obtain a reddish brown powder; S4. The product obtained in step S3 is placed in a heating container for heat treatment, taken out after cooling in the furnace, and etched at room temperature to obtain a porous hollow carbon material.

2. The method for preparing the porous hollow carbon material according to claim 1, characterized in that: In step S1, every 0.1 g of resorcinol corresponds to 20 ml of a mixed solution of ethanol and water, wherein the volume ratio of the ethanol to water is 7:

1.

3. The method for preparing the porous hollow carbon material according to claim 1, characterized in that: In step S1, the volume ratio of the aqueous ammonia solution to the mixed solution of ethanol and water is 3:

80.

4. The method for preparing the porous hollow carbon material according to claim 1, characterized in that: In step S1, the volume ratio of the mixed solution of ethanol and water to the mixed solution of formaldehyde solution and tetraethyl orthosilicate is 80:3.36, wherein the volume ratio of tetraethyl orthosilicate to formaldehyde solution is 5:

1.

5. Porous hollow carbon material, characterized in that: The porous hollow carbon material is prepared by the method for preparing the porous hollow carbon material according to any one of claims 1 to 4.

6. A method for preparing porous carbon / γ-MnO2 electrode material based on EMD, characterized in that: The steps include:

1. Pour EMD and ethanol into a ball mill for ball milling to obtain a gray-black paste, which is then washed and dried to obtain black powder γ-MnO2; 2. Disperse γ-MnO2 and the porous hollow carbon material described in claim 5 in isopropanol, form a suspension after ultrasonic treatment, vacuum filter the suspension to obtain black powder, and dry the black powder to obtain a porous carbon / γ-MnO2 electrode material.

7. The method for preparing porous carbon / γ-MnO2 electrode material based on EMD according to claim 6, characterized in that: In step 2, the mass ratio of the γ-MnO2 and the porous hollow carbon material is 4:

1.

8. The method for preparing porous carbon / γ-MnO2 electrode material based on EMD according to claim 6, characterized in that: In step 2, every 10 ml of isopropanol corresponds to 50 mg of the mixture of γ-MnO2 and the porous hollow carbon material.

9. Porous carbon / γ-MnO2 electrode material, characterized in that: The porous carbon / γ-MnO2 electrode material is prepared by the method for preparing the porous carbon / γ-MnO2 electrode material based on EMD as described in any one of claims 6 to 8.

10. Use of the porous carbon / γ-MnO2 electrode material according to claim 9 in the preparation of zinc ion batteries.